Improving The Methodology of Preparing the Future Technology Teacher for Professional Activity in The Information Education Environment - Farxod, Turabekov (ASEAN Journal of Educational Research and Technology, 2023)
This study discusses and evaluates strategies for improving the methodology of preparing future technology teachers for professional activity in the information education environment. Emphasis is placed on the necessity of these teachers being proficient in modern technologies and methodologies, which form an integral part of today's dynamic educational landscape. The investigation focuses on the exploration of innovative pedagogical methods, the introduction of up-to-date educational technologies, the development of digital competencies, and the fostering of a culture of lifelong learning. The paper analyzes existing pedagogical models and proposes an integrated model for preparing future technology teachers that effectively combines theoretical knowledge and practical skills in the digital domain.